Quaternary protection scheme with optimal dual-directional overcurrent relay setting for smart microgrids - Panida Thararak (2020)
© 2020 Praise Worthy Prize S.r.l. - All rights reserved. The implementation of the microgrid concept with flexible grid-connected and islanded operation in distribution networks creates a variety of protection problems, including mis-coordination, protection blinding, and false tripping. Conventional protection schemes that use traditional overcurrent protective relays cannot respond to the microgrid operations in the manner of short-circuit current changes. In this paper, a novel quaternary protection scheme, along with intelligent electronic device-based dual-directional overcurrent relays, is developed for protecting against faults in microgrids with distributed generations. The proposed protection scheme provides the optimal relay setting groups that rely on the dynamic changes in the microgrid system states and the characteristics of forward and reverse short-circuit currents. The optimal protection coordination is formulated as a non-linear programming optimization problem, which is solved by evolutionary programming. The proposed approach is tested on the IEEE 34-node test feeder, which is modified as the microgrid operation equipped with multiple synchronous-based distributed generations. Test scenarios, including the implementation of different protection schemes and protective devices, are analyzed with different fault locations. The simulation results show that the quaternary protection scheme can overcome all the protection problems. In addition, the significant reduction in the total relay operating times indicates that the proposed protection scheme provides fast fault clearing when compared to the conventional protection approach.